“Do You Really Think Russia Should Pay Up for That?” How the Russia-based TV Channel RT Constructs Russian-Baltic Relations - S. Borchers, Nils (Javnost-The Public, 2011)
Mediated public diplomacy plays an important role in achieving foreign policy objectives by trying to influence public opinion in other countries. The Russia-based global TV channel RT serves as a central tool of Russian mediated public diplomacy. Its objective is not only to present the Russian perspective on different issues but also to propagate it. However, there is not much research on RT in general and none on the strategies RT employs to persuade its viewers of the rightness of the Russian stance. This article explores the use of persuasive strategies in the RT interview show Spotlight. A qualitative content analysis of 15 episodes, which discuss Russian relations to its Baltic neighbours Estonia, Latvia and Lithuania, revealed that Spotlight constructed a one-sided pro-Russian reality. Various strategies are employed to hedge this reality against doubts about its trueness as well as to support Russia’s position in conflicts with the Baltic States. By this, RT aims to isolate the Baltic States internationally in order to help Russia in achieving its foreign policy objectives.